Migraine headaches as a complication of the atrial fibrillation ablation procedure: case report - Sekuła, Michał Jakub; Pawłucki, Piotr; Maciak, Anna; Chyła, Jakub; Smoluchowski, Krzysztof; Sokół, Dorota; Piotrowska, Paulina; Zimna, Aleksandra (Journal of Education, Health and Sport, 2023)
The balloon cryoablation (CA) procedure is an established method for the permanent treatment of atrial fibrillation (AF). Like other surgical interventions, it is associated with the potential development of early and late complications, including neurological ones such as migraine. We report a case of migraine headaches after the CA procedure. 25-year-old man with paroxysmal AF, without comorbidities, underwent balloon CA. On the second day after the procedure, the patient developed visual symptoms typical of migraine aura. After 30 minutes, these symptoms disappeared and appeared classic migraine headache attack. Similar episodes occurred over the following days. A focal central nervous system lesion was ruled out and a diagnosis of migraine with aura was made. The patient received a typical migraine attack treatment. The attacks ceased within two weeks. 3 months later during the follow-up visit at the neurology clinic no abnormalities were detected. We decided to check if the migraine is a rare complication of AF ablation surgery. Many studies do not include migraine headaches at all in the neurological complications of ablation. However, based on some studies, it may seem that the incidence of migraine as a complication of ablation is underestimated.